Development of heterogeneous catalyst from waste for biodiesel production - Shah, Beenish (Kulliyyah of Enginering, International Islamic University Malaysia, 2015)
Homogeneous catalysts have several disadvantages in biodiesel production such as large amount of soap production, it is corrosive to equipment, cannot be reused, produces large amount of wastewater for purification steps, hence increasing the overall cost of biodiesel production. To overcome these problems in production of biodiesel this study looks into alternatives of employing heterogeneous catalyst from waste resources. The waste food material namely crab shell, egg shell and fish bone is selected as heterogeneous catalysts, for biodiesel synthesis by transesterification reaction to determine the source providing the highest biodiesel yield. The solid oxide materials were calcined at 900°C for 2-4 hrs to convert CaCO3 to CaO species. Transesterification was carried out at 65°C for 4 hrs with varied methanol to oil ratio. The optimum calcination time and methanol:oil ratio for transesterification reaction was 3hrs and 12:1 respectively. It was found that although egg shell and crab shell gave average biodiesel yields, fish bone provided the highest yield of the three catalysts. Fish bone catalyst was further chemically treated with Al(NO3)3.9H2O to develop a support for the catalyst in order to enhance the yield and quality of biodiesel. The experiment is designed by face-centered central composite design (FCCCD) under response surface methodology (RSM). The input parameters for process conditions were CaO loading, calcination time for chemically treated catalyst and catalyst wt%. The highest yield of 94.30% was achieved with the optimum conditions at calcination time of 6.11hrs, catalyst wt% of 4.02w/w% and CaO loading of 34.49w/w%. estimated by RSM. This research signifies successful application of waste resources as an emerging prospective for economical preparation of heterogeneous catalyst, developing an unconventional avenue for reusing of this solid waste.